(2y + 1) + (y^2 + 1)
= 2y + 1 + y^2 + 1
= y^2 + 2y + 2
Chat with our AI personalities
3y squared - 2y = 1
It is a quadratic expression and is (2y-1)(3y-4) when factored
If: 3x-2y = 1 Then: 9x^2 = (1+2y)^2 by squaring both sides If: 3x^2 -2y^2 +5 = 0 Then: 9x^2 = 6y^2 -15 by multiplying all terms by 3 So: 6y^2 -15 = 1+4y +4y^2 Transposing and collecting like terms: 2y^2 -16 -4y = 0 Divide all terms by two: y^2 -8 -2y = 0 Factorizing: (y-4)(y+2) = 0 => y = 4 or y = -2 Therefore solutions by substitution are: (3, 4) and (-1, -2)
x+2y = 2 2y = -x+2 y = -0.5x+1 Therefore the slope is -0.5 and the y intercept is 1
11x+2y+9 is the final answer.